SENSUALITAS DALAM KONTEN “YOUTUBE’S GOT TALENT” PADA CHANNEL SKINNYINDONESIAN24 - Syifa Syarifah Alamiyah (LENTERA: JOURNAL OF GENDER AND CHILDREN STUDIES, 2024)
Youtube is a widely accessed new media. During its development, Youtube has enabled its viewers to become producers and consumers. This has resulted in many new profit-oriented content creators, by creating content with sensual elements. This has reaping criticism from previous content creators on Youtube, one of them is SkinnyIndonesian24. This study aims to see how SkinnyIndonesian24 packs a criticism of sensuality through the content "Youtube's Got Talent". This study used descriptive qualitative approach and analyzed using CDA by Norman Fairclough. At the text level, criticism of sensuality is found in clauses, combinations of clauses, relations, and the identity of content creator who’s trying to display. In the discourses analysis level, the text examined by observing the content creator and how the efforts to presenting reality in the content. At the sociocultural practice level, texts are examined by looking at external factors that influence the society interpret something. The conclusion is sensuality content is used as a tool to increase popularity for some content creators on Youtube. The reality in the content illustrates the real enthusiasm of netizens in consuming sensuality content. Unwise packaging of sensuality content only leads to increased popularity and decreased quality of content on Youtube. Keywords: Youtube ; Sensuality ; Content Creator ; Critical Discourses Analysis.